2016
DOI: 10.3174/ajnr.a4740
|View full text |Cite
|
Sign up to set email alerts
|

A Diffusion Tensor Imaging Study on White Matter Abnormalities in Patients with Type 2 Diabetes Using Tract-Based Spatial Statistics

Abstract: Background and Purpose To demonstrate that gradual and continuous WM change and the associated cognitive decline in type 2 diabetes mellitus (T2DM) patients can be captured by DTI parameters and the DTI parameters can be used to complement neuropsychological test scores in identifying T2DM patients with and without mild cognitive impairment (MCI). Materials and Methods Forty-two T2DM patients, divided into a group with MCI (DM-MCI; n = 20) and a group with normal cognition (DM-NC; n = 22) based on cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 32 publications
4
57
2
Order By: Relevance
“…Advanced two-dimensional (2D MRS) methods currently gaining favor are capable of detecting glucose concentrations within specific regions of the brain [179] and may be used some day to study IR in relation to AD. Diffusion MRI has revealed deficits in the microstructural integrity of grey and white matter in AD [180183] and T2D [184186] that are associated with impaired cognitive performance. Functional MRI (fMRI) has been used to demonstrate that insulin infusion enhances neuronal activity in the medial temporal lobe [187], that patients with T2D showed connectivity decreases in regions associated with AD [188, 189], and that higher peripheral insulin levels are associated with less cognitive decline and atrophy in AD patients [190].…”
Section: Clinical Studies On Ir and Admentioning
confidence: 99%
“…Advanced two-dimensional (2D MRS) methods currently gaining favor are capable of detecting glucose concentrations within specific regions of the brain [179] and may be used some day to study IR in relation to AD. Diffusion MRI has revealed deficits in the microstructural integrity of grey and white matter in AD [180183] and T2D [184186] that are associated with impaired cognitive performance. Functional MRI (fMRI) has been used to demonstrate that insulin infusion enhances neuronal activity in the medial temporal lobe [187], that patients with T2D showed connectivity decreases in regions associated with AD [188, 189], and that higher peripheral insulin levels are associated with less cognitive decline and atrophy in AD patients [190].…”
Section: Clinical Studies On Ir and Admentioning
confidence: 99%
“…Through modeling the microscopic diffusion properties of water molecules, different parameters can be estimated, such as fractional anisotropy (FA) and mean diffusivity (MD). Previous DTI studies have demonstrated widespread white matter integrity alterations in several important regions and their correlations with neuropsychological function . It was hypothesized that the FA reductions and MD elevations may reflect axonal degeneration or myelin breakdown in T2DM brains .…”
mentioning
confidence: 99%
“…Previous DTI studies have demonstrated widespread white matter integrity alterations in several important regions and their correlations with neuropsychological function. [12][13][14] It was hypothesized that the FA reductions and MD elevations may reflect axonal degeneration or myelin breakdown in T2DM brains. 13,14 Alternatively, these effects may simply reflect changes in the spatial organization of neurites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructural abnormalities have been published for various brain regions in type 2 diabetes (Yau et al, 2009, 2010; Falvey et al, 2013; Zhang J. et al, 2014, 2016; van Bussel et al, 2016b; Xiong et al, 2016). Reduced FA has been observed in the white matter (Yau et al, 2010; Falvey et al, 2013) mostly concentrated in frontal and temporal regions (Yau et al, 2009), while elevated ADC values were found in a number of brain regions, including the hippocampus (Falvey et al, 2013) and multiple gray matter regions (Yau et al, 2010).…”
Section: White Matter Tract Abnormalitiesmentioning
confidence: 99%